General Formula for limit of square function at infinity - Wibowo, Bonno Andri; Maulidi, Ikhsan; Erliana, Windiani (Universitas Islam Negeri Raden Intan Lampung, 2018)
Determination of the limit value of a function is an important things. Basically, the limit is used to look at the